AKTIVITAS ANTIBAKTERI EKSTRAK PALA DALAM MENGHAMBAT PERTUMBUHAN STREPTOCOCCUS VIDIRANS - Danica Anastasia; Mariatun Zahro Nasution; Rinda Yulianti (Jurnal Kesehatan Gigi dan Mulut (JKGM), 2022)
Background: Antibacterial is a substance that can disturb bacteria growth activity or eliminate it. Nutmeg is one of the natural substances that have antibacterial activity, such as essential oil, saponin, and alkaloid. Objective: This study aimed to determine the antibacterial activity of nutmeg extract in inhibiting Streptococcus viridans growth. Methods: This is a quasi-experimental with posttest only control group design. Distilled water was used as the negative control group; chlorhexidine gluconate 2% was used as the positive control group; the treatment group used nutmeg extract with concentrations of 16%, 12%, 8%, and 4%, respectively. Antibacterial activity testing using agar diffusion (Kirby-Baurer Discs) with Shapiro-Wilk test data analysis, Levene-Test, one-way ANOVA test, and Post-Hoc Test. Result: The result showed that nutmeg extract has an antibacterial effect on the Streptococcus viridans with the most inhibitory zone, at 16% concentration (8,34 mm), while in the positive control the inhibition zone was (17.26 mm). Conclusion: This study concluded that nutmeg extract at a concentration of 16%, 12%, 8%, and 4% have an antibacterial effect in inhibiting the growth of Streptococcus viridans, but is not as effective as chlorhexidine gluconate 2%.